A Principled Approach to Research Conducted with Inuit, Métis, and First Nations People: Promoting Engagement Inspired by the CIHR Guidelines for Health Research Involving Aboriginal People (2007-2010) - Jull, Janet; King, Alexandra; King, Malcolm; Graham, Ian D.; Morton Ninomiya, Melody E.; Jacklin, Kristen; Moody-Corbett, Penny; Moore, Julia E. (The International Indigenous Policy Journal, 2020)
Research to address the health burdens experienced by Indigenous populations is essential. In the Canadian context, the Truth and Reconciliation Commission of Canada determined that these health burdens are the result of policies that have undermined opportunities to address community-level health needs. The Canadian Institutes of Health Research Guidelines for Health Research Involving Aboriginal People (2007-2010), or“CIHR Guidelines,” were prepared in a national consultation process involving Inuit, Métis, and First Nations communities, researchers, and institutions. This paper asserts that the principles espoused in the CIHR Guidelines hold ongoing potential to guide health research with Indigenous people in ways that promote equitable research partnerships. We encourage those in research environments to engage with the spirit and content of the CIHR Guidelines.